Clinicodemographic Features of Plica Neuropathica: A Cross-Sectional Prospective Study - Mohammed A. El-Hamd; Rasha I. Mohamed (Wolters Kluwer Medknow Publications, 2024)
Background: Plica neuropathica (PN) is an acquired hair disorder characterized by sudden onset, irreversible hair matting, which seems to be a compact hair mass with irregular twists. Aim and Objective: This study aimed to evaluate the clinicodemographic features of PN. Materials and Methods: This study was a cross-sectional prospective clinical research that included patients with PN. All the included patients were subjected to a detailed history of clinicodemographic data and clinical with trichoscopic examinations of the affected hair and scalp. Results: This study included 18 female patients with PN, with a mean age of 23.94 ± 7.9 years. All the patients presented with PN had acute onset and progressive course, psychological stressful factors preceding PN, negligence of hair care, no history of hair care product use, no history of hair straightening, no previous treatment preceding PN, and no history of systemic diseases. Recurrence of PN was reported in 4 (22.2%) patients. On trichoscopic evaluation, all patients were presented with normal scalp and matting of hair shaft with honey-colored concretions mimicking the "wrangled mesh of wires" appearance. Sixteen (88.9%) patients were treated with cutting hair mass. Most of the included patients reported very large and extremely large effects on the quality of life. Conclusion: This study concluded that PN is an uncommon acquired hair matting disorder prevalent in young age females. It is associated with marked impairment of the patient's quality of life. Psychological stressful factors and negligence of hair care are the main risk factors for PN. Regular hair care measures are essential to prevent hair matting.